2011
DOI: 10.1080/14742837.2011.614104
|View full text |Cite
|
Sign up to set email alerts
|

The Tea Party Movement, Framing, and the US Media

Abstract: In February 2009, the Tea Party Movement (TPM) burst onto the political scene in the USA. Emerging out of popular unrest over the economic downturn of 2008 and the perceived radical agenda of President Barack Obama, the Tea Party quickly captured the imagination of disenchanted conservatives. Media coverage of the movement was abundant, with a frame contest between the TPM and its political opponents swiftly surfacing. Media frames bracketed discussions over the authenticity of the Tea Party, the composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 29 publications
1
68
1
Order By: Relevance
“…In a study by Weaver and Scacco (2013) on the Tea Party movement, findings indicated that MSNBC program hosts were more likely to marginalize the Tea Party than CNN or FOX hosts, calling its members "idiots" and questioning the grassroots nature of Tea Party membership. Boykoff and Laschever (2011) similarly found that a "non-mainstream frame" was used more frequently by MSNBC news sources than an "everyday American frame" to describe Tea Party members.…”
Section: Cable News Pundits and Divisive Languagementioning
confidence: 94%
“…In a study by Weaver and Scacco (2013) on the Tea Party movement, findings indicated that MSNBC program hosts were more likely to marginalize the Tea Party than CNN or FOX hosts, calling its members "idiots" and questioning the grassroots nature of Tea Party membership. Boykoff and Laschever (2011) similarly found that a "non-mainstream frame" was used more frequently by MSNBC news sources than an "everyday American frame" to describe Tea Party members.…”
Section: Cable News Pundits and Divisive Languagementioning
confidence: 94%
“…This phenomenon, which shapes Congressmen's behaviour, is what is known as Fenno's paradox-voters generally disapprove of Congress as a whole but support the Congressmen from their own district (Fenno, 2002). Anti-establishment politics are not new (Horwitz, 2013;Barr, 2009) and can currently be observed both in the conservative right with the Tea Party members (Boykoff and Laschever, 2011;Skocpol and Williamson, 2012), as well as in the liberal left (Bolton, 2016). However, members of Congress become institutionalized and their behaviour is shaped by their institution (Binder, 2015;Hibbing and Theiss-Morse, 1995;Canon, 1989) even as they campaign as outsiders (Herrnson, 2007;Burden, 2004).…”
Section: Related Workmentioning
confidence: 99%
“…Sparked by a call by a conservative commentator for a “Chicago Tea Party” in response to the Obama administration's plans for a mortgage assistance program, Tea Party websites and organizations sprouted up like mushrooms. In particular, the large grassroots component of Tea Party groups flowed together with large, national funding sources and the conservative media—and making use of rhetorical formations previously developed by conservatives (Williamson, Skocpol, and Coggin ; Zernike )—to focus on the contestation of Republican primaries, especially in the 2010 midterm elections (Boykoff and Laschever ; Fetner and King ; Miller and Walling ; Perrin et al. ).…”
Section: The Tea Party and Occupymentioning
confidence: 99%
“…In some cases, such realignments can take place comfortably within the existing party system. An important example here involved the realignment of the American South in the twentieth century (Black and Black 2002;Kawato 1987;Petrocik 1987;Shafer and Johnston 2006 later, in local ones), presumably because the latter appeared less supportive of continued civil rights legislation. But in other cases, we expect that there is a time when, for some citizens, there is no party that they believe can represent their ideological positions.…”
Section: Alternative Alternativesmentioning
confidence: 99%